2004
DOI: 10.1158/1535-7163.1533.3.12
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of constitutive signal transducer and activator of transcription 3 activation by novel platinum complexes with potent antitumor activity

Abstract: DNA-alkylating agents that are platinum complexes induce apoptotic responses and have wide application in cancer therapy. The potential for platinum compounds to modulate signal transduction events that contribute to their therapeutic outcome has not been extensively examined. Among the signal transducer and activator of transcription (STAT) proteins, Stat3 activity is frequently up-regulated in many human tumors. Various lines of evidence have established a causal role for aberrant Stat3 activity in malignant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 168 publications
(25 citation statements)
references
References 50 publications
0
23
0
Order By: Relevance
“…300 Turkson et al reported that platinum-containing compounds can selectively block STAT3, and it has been shown that platinum (IV)-containing complexes, CPA-1 and CPA-7, disrupt the DNA-binding capacity of STAT3 and induce tumor regression. 301 Recently, a novel smallmolecule lead compound called (E)-2-methoxy-4-(3-(4methoxyphenyl)prop-1-en-1-yl)phenol (MMPP) was synthesized by Son et al, and it can suppress cancer growth by directly interacting with the DBD of STAT3. 256 Compared to the bioactive compound (E)-2,4-bis(p-hydroxyphenyl)-2-butenal (BHPB), which was synthesized previously, MMPP circumvented the problem caused by the presence of α, β-unsaturated carbonyl groups in BHPB that form a non-selective covalent bond, which is conducive to side effects.…”
Section: Blocking Dimerizationmentioning
confidence: 99%
See 1 more Smart Citation
“…300 Turkson et al reported that platinum-containing compounds can selectively block STAT3, and it has been shown that platinum (IV)-containing complexes, CPA-1 and CPA-7, disrupt the DNA-binding capacity of STAT3 and induce tumor regression. 301 Recently, a novel smallmolecule lead compound called (E)-2-methoxy-4-(3-(4methoxyphenyl)prop-1-en-1-yl)phenol (MMPP) was synthesized by Son et al, and it can suppress cancer growth by directly interacting with the DBD of STAT3. 256 Compared to the bioactive compound (E)-2,4-bis(p-hydroxyphenyl)-2-butenal (BHPB), which was synthesized previously, MMPP circumvented the problem caused by the presence of α, β-unsaturated carbonyl groups in BHPB that form a non-selective covalent bond, which is conducive to side effects.…”
Section: Blocking Dimerizationmentioning
confidence: 99%
“…Turkson et al. reported that platinum‐containing compounds can selectively block STAT3, and it has been shown that platinum (IV)‐containing complexes, CPA‐1 and CPA‐7, disrupt the DNA‐binding capacity of STAT3 and induce tumor regression 301 . Recently, a novel small‐molecule lead compound called (E)‐2‐methoxy‐4‐(3‐(4‐methoxyphenyl)prop‐1‐en‐1‐yl)phenol (MMPP) was synthesized by Son et al., and it can suppress cancer growth by directly interacting with the DBD of STAT3 256 .…”
Section: Stat3 As a Therapeutic Target In Cancer Treatmentmentioning
confidence: 99%
“…Each monomer within an active STAT3 dimer has a total of four loops, three from the DBD and one from the linker domain that form interactions with the double helix of DNA . Platinum compounds are known to form DNA adducts and therefore can disrupt the ability of STAT3 to bind DNA, leading to apoptosis in STAT3 dependent human cancer cell lines. , Platinum compounds proposed as STAT3 inhibitors are classified as platinum­(IV) complexes and differ from chemotherapeutics such as cisplatin, a platinum­(II) complex, which displays no inhibitory effect on STAT3. , The most well-known platinum­(IV) DBD inhibitors are CPA-1, CPA-7, and platinum­(IV) tetrachloride. More recently another platinum­(IV) compound, IS3–295, was determined to inhibit the DNA-binding capacity of STAT3 although its mechanism of action still requires elucidation .…”
Section: Direct Stat3 Inhibitorsmentioning
confidence: 99%
“…8 Platinum compounds are known to form DNA adducts and therefore can disrupt the ability of STAT3 to bind DNA, leading to apoptosis in STAT3 dependent human cancer cell lines. 86,87 Platinum compounds proposed as STAT3 inhibitors are classified as platinum(IV) complexes and differ from chemotherapeutics such as cisplatin, a platinum(II) complex, which displays no inhibitory effect on STAT3. 86,87 The most well-known platinum(IV) DBD inhibitors are CPA-1, CPA-7, and platinum(IV) tetrachloride.…”
Section: Acs Chemical Biologymentioning
confidence: 99%
See 1 more Smart Citation